2003
DOI: 10.1521/pedi.17.3.263.22152
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Rejecting and Treatment Seeking Personality Disorders: Type R and Type S

Abstract: An important distinguishing feature of one group of personality disorders is the wish of the sufferer to seek treatment. For another group this wish is rarely entertained. Although there is some variation between different types of personality disorder the wish to change is not confined to any one diagnostic category. A useful subclassification of personality disorders is therefore into Type R (treatment rejecting) and Type S (treatment seeking) personality disorders, and these are defined operationally. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 8 publications
5
111
1
2
Order By: Relevance
“…Less than one in three patients with a personality disorder are type S (treatment seeking), most are type R (treatment resisting), 20 and the proportion in the ordinary population is only around one in five (Kirby et al, to be published). This sometimes appears odd to those who see lives devastated by those who have these conditions, but sufferers often show a surprising lack of awareness of the consequences of their behaviour and frequently remain indifferent or blame others for the chaos and distress that follows their actions and interactions.…”
Section: Available Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than one in three patients with a personality disorder are type S (treatment seeking), most are type R (treatment resisting), 20 and the proportion in the ordinary population is only around one in five (Kirby et al, to be published). This sometimes appears odd to those who see lives devastated by those who have these conditions, but sufferers often show a surprising lack of awareness of the consequences of their behaviour and frequently remain indifferent or blame others for the chaos and distress that follows their actions and interactions.…”
Section: Available Treatmentsmentioning
confidence: 99%
“…This particularly applies to those with antisocial (dissocial) personality disorder, 9 out of 10 of whom do not want any form of treatment spontaneously. 20 This number rises to nearly 50% when there is an element of coercion involved, as for example in the DSPD programme where prisoners feel that early parole may be given if they cooperate with a treatment programme, but is unlikely to represent a true expression of their wishes. 25 A new intervention, nidotherapy (from nidus, L. 'nest'), has recently been introduced which does not attempt to change patients' symptoms or behaviour directly but instead concentrates on changing the environment in a systematic and collaborative way.…”
Section: Treatments For Type R Personality Disordersmentioning
confidence: 99%
“…Furthermore, the high dropout rates due to pronounced sensitivity to side effects in this population, and the lack of sufficient statistical power to assess treatment efficacy hamper interpretations of the results. It has been suggested that differences in patients willingness to receive treatment may account for the variation between the amount of evidences of treatment efficacy for different personality disorders [143]. Thus, while BPD patients often present with demands to be treated, only 1 out of 10 patients with paranoid and schizoid personality disorder is prone to treatment, hence the large difference in research proportion for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while BPD patients often present with demands to be treated, only 1 out of 10 patients with paranoid and schizoid personality disorder is prone to treatment, hence the large difference in research proportion for these disorders. It may be therefore useful to differentiate between treatment-seeking and treatment-resisting patients with personality disorders [143].…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of nidotherapy is that motivation to change, one of the requirements for success with most complex treatments, is not necessary, as there is no direct attempt to change the person, only the surroundings, to effect a better match. This is of great help in the treatment of those with personality disorders, most of whom are treatment-resisting (Type R) rather than treatmentseeking (Type S) (Tyrer et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%